Differences in the quality of life of women regarding their source of income – agriculture vis-a-vis non-agriculture - Majda ČERNIČ ISTENIČ (Acta Agriculturae Slovenica)
Over the last fifty years the share of population engaged in agriculture has decreased significantly in Slovenia due to intensive industrialisation and urbanisation. Today this trend is still going on and the prognosis for many farm lands are sparsely populated settlements. One of the reasons for the present depopulation of Slovenian farmers certainly lies in unwillingness of many young women to form a farm family and to make a living by farming. For better understanding of factors that divert young women from decisions to marry and to live on the farm it is necessary to know how the living conditions of farm women differ from those who make their living in other ways. In order to find out these differences the data set "Quality of Life in Slovenia - retrospective study 1974-1994" was used and the Allardt's concept of well-being that distinguishes between having (material conditions) loving (relations with the other people), being (the need for personal development) and (dis)satisfactions on different spheres of individual’s life was applied.